THE IMPLEMENTATION OF TOLERANCE CULTURE BY ISLAMIC EDUCATION TEACHERS TOWARD STUDENTS AT SMA NEGERI 1 POSO - Suriyanto, Suriyanto; Pettalongi, Adawiyah; Saude, Saude; Mustaan, Mustaan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
Several incidents that have occurred in recent times in this country strongly suggest that differences are often used as a tool for provocation, leading to unnecessary tension and violence. Therefore, tolerance has become an urgent necessity that the Indonesian nation must prioritize by redefining attitudes of tolerance, particularly in the context of religion, appropriately within a pluralistic society. This thesis examines the implementation of tolerance culture by Islamic Education teachers towards students at State Senior High School 1 Poso. The findings reveal that the forms of tolerance practiced by teachers and students include helping peers in need, respecting those with different beliefs, refraining from disrupting peers performing religious rituals at school or outside school, visiting and praying for sick friends, and visiting social care homes of different religious backgrounds. The implementation of a tolerance culture by Islamic Education teachers at State Senior High School 1 Poso is carried out through teaching and setting examples for students to respect, care for, and appreciate diversity. This culture is integrated into the teaching-learning process both inside and outside the classroom. The impact of this tolerance culture is highly positive, fostering mutual respect and regard between students and teachers. It has created a safe, peaceful, comfortable, and conducive school environment, positively influencing the learning process. Based on these findings, the author recommends that the school principal, Islamic Education teachers, students, and all stakeholders work together to maintain and implement the culture of tolerance both within and beyond the school environment.